Ladder-Type Benzene-Perylene Dyes with Eﬃcient LaserProperties in the Near-IR by Detracting/ActivatingLow/High Frequency Vibronic Modes - Díaz-Fernández, Marcos; Farrando-Pérez, Álex; Gordillo Gámez, Fernando; Boj, Pedro G.; Villalvilla Soria, José Moisés; Quintana, José A.; Wan, Yanpei; Aranda, Daniel; Marín-Beloqui, José Manuel; Wu, Jishan; Zen, Zebing; Díaz-García, María A.; et al. (Wiley, 2025)
Organic lasers are very attractive light sources for various applications, which have propelled the search for organic compounds showing good performance as active laser units. Here, a family of ladder-type oligomers (named as NNR-n with n = 1–4), constructed by benzene and perylene is presented. These molecules show outstanding amplified spontaneous emission properties in terms of threshold and photostability, being particularly noticeably the larger size molecules emitting in the near infrared (NIR) region. The origin of this behavior is elucidated through comprehensive spectroscopic and theoretical characterization investigating the underlying photophysical processes using steady-state absorption and emission measurements at both room temperature and cryogenic conditions, complemented by transient absorption spectroscopy spanning the visible to near-infrared (vis-NIR) regions. The results demonstrate that the excited-state electronic dynamics are governed by high-frequency vibrational modes. The rigid ladder-type structure suppresses low-frequency vibronic coupling modes, thereby significantly reducing internal conversion, which enhances NIR emission by promoting efficient radiative pathways. Finally, distributed feedback lasers have been made to exploit such optical properties resulting in devices with lasing up to 758 nm.
Keywords: Química física; Fotónica; Espectroscopía; amplified spontaneous emission; benzene perylene oligomers; distributed feedback lasers; ladder-type π−conjugated oligomers; spontaneous fluorescence; vibronic progressions